Analisis Pengaruh Locus of Control dan Stres Kerja Terhadap Kinerja Pegawai Bagian Kesejahteraan Rakyat Setdakar Tulang Bawang - Safitri, Nazella; Soedarsa, Herry Goenawan (Jurnal EMT KITA, 2023)
In the success of an organization, the role of individuals becomes very important. Employee satisfaction and productivity are key factors that influence an organization's overall results. There are two important factors that influence employee engagement, which are work stress and the individual's locus of control. The purpose of this study was to explore how employees of the People's Welfare Department of the Tulang Bawang Regional Secretariat responded to workplace stress and their locus of control. The research method used was quantitative research in the research population consisting of the staff of the People's Welfare Department of the Tulang Bawang Regional Secretariat. Data were collected through questionnaires and multiple regression analysis was used to process the data. Research results show that locus of control (X1) and work stress (X2) have a significant impact on employee performance, in which locus of control is the factor with the greatest influence. in this study.